Maintenance of haemocytes of edible oyster, Crassostrea madrasensis (Preston) in artificial media - Ittoop, Gijo; George, K C; Sanil, N K; Shobhana, K S; Nisha, P C (Indian Journal of Fisheries, 2011)
The haemocytes of Crassostrea madrasensis were maintained in Hank's balancedsalt solution (HBSS), HBSS with 10% foetal calf serum (FCS), tissue culturemedia M 199, and M 199 with 10% FCS. Total counts of viable haemocytes weretaken at 0 hr, 24 hrs, 48 hrs, and 72 hrs. HBSS and HBSS with 10% FCS werefound to maintain cell viability upto 72 hrs without much reduction in the countof viable cells. In M199 and M199 with 10% FCS, it was found that a substantialincrease of small hyalinocytes occurred at 24 hrs and 48 hrs. This was followed bya steep fall in the number of viable cells at 72 hrs in both the media. The HBSS,HBSS with 10% FCS, M199 and M199 with 10% FCS were found to be good formaintaining the cells in viable state. However, only M 199 and M 199 with 10%FCS indicated multiplication of haemocytes.